Degraded polysaccharide from Lycium barbarum L. leaves improve wheat dough structure and rheology. (June 2021) - Al-Wraikat, Majida; Hou, Chen; Zhao, Guangtao; Lu, Hao; Zhang, Hengkai; Lei, Yanan; Ali, Zeshan; Li, Jianke
Abstract: Lycium barbarum L. leaves contain high amounts of mineral rich polysaccharides. In this study, the crude and the degraded polysaccharide using hydrogen peroxide (H2 O2 ) and vitamin C were prepared and tested as additives to investigate their effects on the quality of wheat dough using rheological assays. Polysaccharides, in particular degraded polysaccharide, significantly promoted the texture properties and extensographic characteristics of wheat dough compared to the control (p < 0.05), indicating an improvement in dough strength. The gluten networks in the dough samples exhibited dramatically dense and tight characteristics. This could be attributed to the formation of disulfide bonds triggered by the crude and degraded polysaccharides. Besides, analysis revealed that polysaccharides conformation played a major role in the transformation of the protein secondary structures from β-sheets to β-turns and α-helixes. Results demonstrated that the chemical degradation of polysaccharide could greatly improve the gluten network of wheat dough. Highlights: Polysaccharides promoted wheat dough texture and extensographic properties. Chemical degradation improved polysaccharide's dough modulation additive usage. Polysaccharide confirmation affected its food additive functional bioactivity. Degradation improved the functional bioactivity of polysaccharide as a food additive. Dough rheology behavior can be alternated significantly by degraded polysaccharide.